Analisis Kontrastif Isim Dhomir Dalam Bahasa Arab Dan Kata Ganti Dalam Bahasa Indonesia Serta Langkah-Langkah Pembelajarannya - Ulfa Humaira; Muhammad Singgih; Muhammad Irham (Al Mitsali, 2023)
The background of this research is due to the contrast between the isim dhomir in Arabic and pronouns in Indonesian which may cause errors and difficulties in learning Arabic. In this research, the researcher examines the contrastive analysis between the isim dhomir in Arabic and pronouns in Indonesian accompanied by an explanation of the steps for learning the isim dhomir. This research includes library research using contrastive and descriptive analysis to analyze the data. Broadly speaking, the findings through contrastive analysis include: 1) In B1 (first language: Arabic) accommodates different forms of pronouns that are used to replace the subject with pronouns to replace objects and signs of ownership, while in B2 (second language: Indonesian) the form of pronouns can be used in all circumstances , both subject, object and, sign of ownership. 2) In B1 it accommodates gender differences, while in B2 it doesn’t. 3) B1 and B2 have the same rules, namely: the placement of the pronoun that functions as an object is after the verb and the pronoun that functions as a sign of ownership is after the noun. The appropriate learning steps to be applied use the qowaid wa al-tarjamah learning steps.